An experimental based optimization of a novel water lean amine solvent for post combustion CO2 capture process. (15th August 2019) - Hwang, Junhyeok; Kim, Jeongnam; Lee, Hee Won; Na, Jonggeol; Ahn, Byoung Sung; Lee, Sang Deuk; Kim, Hoon Sik; Lee, Hyunjoo; Lee, Ung
Graphical abstract: Highlights: Propose a new water lean amine solvent for CO2 capture. The low regeneration energy of K2 Sol is demonstrated through pilot plant operation. K2 Sol presents superior performances about cyclic capacity and thermal stability. GPBO is used as a new way to optimize operating conditions in pilot-scale testing. K2 Sol requires only 65% of regeneration energy of MEA. Abstract: The development of new amine solvents without the major drawbacks of conventional amines is crucial to industrial applications of CO2 capture. This paper presents a water-lean CO2 capture solvent having a low regeneration energy and low degradation. The water-lean solvent, K2 Sol, is a sterically hindered diamine; because of the hindered amine site, K2 Sol easily forms bicarbonate, resulting in a high absorption capacity. The minimum solvent regeneration energy is obtained using Gaussian process Bayesian optimization (GPBO) and bench-scale pilot plant experiments. GPBO finds the optimal solution using the input and output relationship of experiments; thus, expensive first-principle model construction can be avoided. According to the pilot plant experiment, the optimal regeneration energies of monoethanolamine (MEA) and K2 Sol are 4.3 and 2.8 GJ/t CO2, respectively, indicating that K2 Sol requires only 65% of the regeneration energy of MEA. Fewer than 30 experiments are required to find the optimal pilot plant operation for both the MEA and K2 Sol experiments. We also describe the superior properties of K2 Sol in terms of the CO2 loading, cyclic capacity, regeneration temperature, and degradation.